Nonconsequentialist Precaution - Morgan-Knapp, Christopher (Ethical theory and moral practice, 2015)
How cautious should regulators be? A standard answer is consequentialist: regulators should be just cautious enough to maximize expected social value. This paper charts the prospects of a nonconsequentialist - and more precautionary - alternative. More specifically, it argues that a contractualism focused on ex ante consent can motivate the following regulatory criterion: regulators should permit a socially beneficial risky activity only if no one can be expected to be made worse off by it. Broadly speaking, there are two strategies regulators can use to help risky activities satisfy this criterion: regulators can mandate strict safety standards that protect those who would otherwise stand to lose, and they can require that some of the benefits of the activity be redirected to them. In developing these themes, the paper aims to provide a theoretical grounding for those who oppose using risk-cost-benefit analysis as the primary regulatory standard, and in particular, for advocates of the precautionary principle.